MODERN LABORATORY DIAGNOSIS PATIENTS WITH THE RHEUMATIC DISEASES - Maxmatov Maxmudjon Farxodovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Obtaining objective information about the presence and nature of immunopathologic changes in the examined patient, which is an important tool for early diagnosis, assessment of activity, severity of course, prognosis of the disease and effectiveness of therapy [1,2].